Eksistensi Aqidah Dalam Pendidikan Islam dan Sebab-Sebab Penyimpangannya - Evan Silalahi; Muhammad Rendy Alfiansyah; Hafiz Pradana; Ahmad Fauzan Halim; Muhammad Mazlan (Pusat Riset dan Inovasi Nasional, 2024)
Aqidah is a principle of faith that has been established by Allah SWT. And we as human beings are obliged to believe in it in order to be worthy of being called believers. But that does not mean that faith is dogmatically instilled in humans, because the process of faith must be accompanied by aqli postulates. But because human reason is limited, not everything that can be trusted can be perceived and achieved by human reason. Scholars agree that the aqli proposition can indeed give birth to strong faith and faith. While the naqli postulate that can produce the desired belief is only the qath'i postulate. This short article presents some discussions that may be useful for those who want to understand the aqidah.